The issue of cultural code in expressive means of newspaper and publicistic style - Teshabaуeva D. M.; Zulpukarov, K. Z.; Sabiraliyeva, Z. M. (The Lingua Spectrum, 2025)
The relevance of the problem lies in the need to address the peculiarities of expressive means functioning in newspaper texts. The study of expressive means in newspaper texts remains extremely relevant, as they play a key role in shaping media style. Stylistic analysis has shown that expressive devices not only create a holistic perception of newspaper-journalistic style but also enhance the expressiveness of publications. This style, inherent to mass media, skillfully combines precise facts, topicality, and emotional vibrancy to address a wide audience. Its goal is not only to inform but also to shape public opinion. Research on expressiveness revealed that one of the main functions of such tools is to highlight key elements of the text, which helps the media effectively influence readers. The purpose of the article is to explore the role of cultural code in the use of expressive means in newspaper-journalistic style. The work aims to analyze how expressive devices imbued with cultural meanings contribute to enhancing the emotional impact of media texts, shaping public opinion, and highlighting key ideas while reflecting the unique values and worldview of the target audience.